Predicting the Level of Marital Conflicts Based on Anxious-Insecure Attachment Style: The Mediating Role of Interpersonal Mindfulness - Gholizadeh Onsoroudi, Tayebeh; Etemadinia, Mahin; Farshbaf Manisefat, Farnaz (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Various studies have examined the multiple factors through which couples' attachment styles can play a role in creating marital conflicts. In the present study, the mediating role of interpersonal mindfulness is investigated as a factor that may explain part of the role of anxious-insecure attachment style in creating marital conflicts among couples. Methods and Materials: In this correlational-descriptive study, a total of 402 couples who visited counseling centers in Tehran in 2023 were selected using convenience sampling. They responded to the Interpersonal Mindfulness Scale (Pratscher et al., 2019), the Revised Experiences in Close Relationships Questionnaire (Fraley et al., 2000), and the Kansas Marital Conflict Scale (Eggman et al., 1985). Data analysis was done using structural equation modeling. Findings: Findings indicated that anxious-insecure attachment style affects marital conflict both directly and indirectly through interpersonal mindfulness. Additionally, anxious-insecure attachment style and interpersonal mindfulness explain 20% and 16% of the variance in marital conflict, respectively. Conclusion: The findings of this study indicated that interpersonal mindfulness mediates the relationship between anxious-insecure attachment style and marital conflicts among couples. The results of this research suggest that couples with an anxious-insecure attachment style experience more marital conflicts due to a lack of interpersonal mindfulness.